Penyelenggaraan Kelas Ibu Hamil Sebagai Realisasi Penganggaran Dana Desa Di Wilayah Kerja Puskesmas Sungai Turak - Siti Khodijah; Meldawati Meldawati; Siti Noor Hasanah (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
One of the health services needed by pregnant women is maternal and child health counseling. The pregnant women class is a means to learn together about health for pregnant women, in the form of face-to-face in groups that aim to improve mothers' knowledge and skills regarding pregnancy, pregnancy care, childbirth, postpartum care, newborn care, myths, infectious diseases and birth certificates. The class for pregnant women coordinated by the Sungai Turak village health center is considered less than optimal, where the level of attendance and motivation of mothers in participating in classes for pregnant women is considered to be lacking. Other facilities are also needed that can support the implementation of classes for pregnant women. The resolution of obstacles or obstacles is to cooperate with village institutions (Village Government, Village Consultative Bodies, and Village Community Institutions), to include the budget for pregnant women classes in the Village Revenue and Expenditure Budget (APB). Based on the results of discussions with village officials, it was decided to include some proposals for pregnant women classes in the Village Revenue and Expenditure Budget (APB).